CO₂ and HDPE Upcycling: A Plasma Catalysis Alternative - Gorky, Fnu; Nambo, Apolo; Kessler, Travis J; Mack, J Hunter; Carreon, Maria L. (Industrial & engineering chemistry research, 2023)
This work describes the use of CO₂ plasma as an active directing agent toward high-density polyethylene (HDPE) decomposition to synthetic fuels. We present for the first time the possibility of taking advantage of the electric field when using perovskites, a material responsive to such types of electrical inducement. Perovskites are observed to provide control of the reactive species by increasing the adsorption of the plasma-polarized CO₂ due to their polar crystallographic unit cell that can generate an electric polarization modulated by the external electric field. Moreover, the plasma exposure charges the perovskite surface, and the accumulation of electrons promotes the generation of oxygen vacancies and thus a high conversion of CO₂. The perovskite then leads to an improved intensity of the plasma-generated species prone to initiating HDPE decomposition such as O atoms and CO. This plasma-generated initiator directs random scissions, resulting in condensates that have the potential to be used as synthetic fuels as our product stream contains C₅-C₁₁ hydrocarbons similar to naphtha, which can be blended into gasoline; C₉-C₂₀ hydrocarbons with higher cetane numbers, similar to diesel; and C₂₀₊ waxes, which can also be converted into alternative fuel diesel through hydrocracking. We expect this work to initiate the development of tailored materials responsive to electric fields for important sustainable applications, where CO₂ might play an important role.